DECISION-MAKING FOR TREE REMOVAL IN URBAN DEVELOPMENT: INSIGHTS FROM LOCAL AUTHORITIES IN MALAYSIA - Hassan, Khalilah; Wan Mohamad, Wan Saiful Nizam; Hasan, Ramly; Bahaluddin, Azrul (PLANNING MALAYSIA, 2024)
The decision to remove trees in development areas can avoid various risks caused by problem trees, but also involves the risk of losing valuable trees. This paper aims to investigate decision-making practices in relation to existing trees in development areas and identify the factors that influence those decisions. Data were collected through semi-structured interviews with landscape architects from selected local authorities and analysed using thematic analysis. Only local authorities requiring a tree preservation survey for landscape plan applications and landscape architects participated in this study. The results show that all factors influencing tree removal decisions are interrelated and vary according to the circumstances. Lack of authoritative resources and spatial constraints have affected the rationality of tree retention decisions and led to tree removal. This study contributes to urban tree retention theory and may improve tree preservation and management strategies. Future research should explore the perspectives of other construction professionals to refine each of the results and conclusions.